More Than Just a Spawning Location: Examining Fine Scale Space Use of Two Estuarine Fish Species at a Spawning Aggregation Site - Boucek, Ross E.; Leone, Erin; Bickford, Joel; Walters-Burnsed, Sarah; Lowerre-Barbieri, Susan (Frontiers in Marine Science, 2017)
Many species that provide productive marine fisheries form spawning aggregations. Aggregations are predictable both in time and space and constitute nearly all of the reproductive activity for these species. For species that spend weeks to months on spawning aggregation sites, individuals may need to rely on a forage base at or near the spawning site to balance the high energetic cost associated with reproduction. Here, we ask: do spawning fish with protracted spawning seasons use spawning aggregation sites more or less than adjacent foraging habitats? To answer our research question, we tracked 30 Snook (Centropomus undecimalis) and 29 Spotted Seatrout (Cynoscion nebulosus) at a spawning site during the 2007 spawning season in Tampa Bay (Fl, U.S.) using acoustic telemetry. We quantified the amount of time both males and females of both species spent in various habitats with network analyses. Surprisingly, results from network analyses revealed that receivers with the highest edge densities for Snook and Seatrout occurred within the seagrass habitat, not the location of spawning. Likewise, we found that both Snook and Seatrout during the spawning season were using the seagrass habitat near the spawning site as much, or more than the location where spawning occurs. Our results show that if protected areas are formed based on only where spawning occurs, the reproductive stock will not be protected from fishing. Further, our results suggest that spawning aggregation sites and areas surrounding used by fishes, may have multiple ecological functions (i.e. larval dispersal and energy provisioning) that may need to be considered in conservation actions. Our case study further supports hypotheses put forth in previous work that suggest we must consider more than just spawning sites in protected area development and ecological conservation.